Towards legal compliance of electronic records management & electronic discovery readiness National Conference On Electronic Evidence, 14th February 2006, Conference Hall, Perbadanan Putrajaya Complex. - National Conference On Electronic Evidence (2006 : Putrajaya); Universiti Teknologi MARA (Putrajaya : Universiti Teknologi MARA, 2006)
Contains papers presented in National Conference On Electronic Evidence. also included Electronic Discovery and Computer Forensics Case Law.
Keywords: Electronic evidence -- Congresses; Electronic records -- Management -- Congresses; Records -- Management -- Congresses; Evidence, Criminal -- Congresses